Тhe efficacy of a formulation derived from Artemisia lerchiana in the treatment of wounds in animals - Yertleuova, B. O. (Zhangir khan West Kazakhstan Agrarian-Technical University, 2025)
The monograph examines the safety of the wormwood (Artemisia lerchiana) plant for the organism, its therapeutic effectiveness in veterinary medicine and human healthcare, and its accessibility in both market conditions and everyday household use. For the first time in the West Kazakhstan region, the antimicrobial effect of the endemic Artemisia lerchiana species-commonly found in this area-has been identified and its pharmacotoxicological safety has been confirmed. A new effective medicinal preparation for treating common surgical wounds among animals in veterinary surgery is proposed. This monograph is recommended for veterinary professionals in the field, as well as for master’s and doctoral students to apply in their practical work. Additionally, it is suggested as a resource for students studying the subjects of «Veterinary surgery» and «Pharmacology and toxicology» within the 6B09100 – «Veterinary medicine» educational program.
Yertleuova, B. O. Тhe efficacy of a formulation derived from Artemisia lerchiana in the treatment of wounds in animals : monograph / B. O. Yertleuova. - Uralsk : Zhangir khan West Kazakhstan Agrarian-Technical University, 2025. - 111 p. - ISBN 978-601-319-630-5
Keywords: rk; veterinary medicine; zhangir khan west kazakhstan agrarian-technical university; ветеринария; artemisia lerchiana; veterinary surgery; monograph